Detection and preliminary characterization of antibacterial protein(s) in the serum of mud crab, Scylla serrata - Meiyalagan, V.; Arumugam, M. (Invertebrate Survival Journal, 2015)
Serum of mud crab, Scylla serrata has been found to possess significant antibacterial activity against some of the resident specific bacteria including Bacillus sp. N1, Bacillus flexus N3, Escherichia coli as well as crustacean pathogenic bacteria viz., Vibrio harveyi, V. alginolyticus and V. vulnificus. The physico-chemical characterization reveals the molecule responsible for antibacterial activity in the serum over 14 kDa, stable in the pH range of 6 to 8 and between the temperatures 20 to 40 degrees C. Precipitation of respective molecule(s) with 75 % ammonium sulphate or the supernatant obtained after precipitating the protein with 10 % TCA indicated that the molecule(s) responsible for serum antibacterial activity appear to be proteinaceous in nature. Further studies demonstrated that antibacterial molecule(s) against E. coli and V. harveyi appeared to be trypsin and pronase resistant and the molecule(s) or domain responsible for antibacterial activity against Bacillus sp. N1 and B. flexus N3 appeared to be protease sensitive, thereby implicating possible involvement of multiple antibacterial factors in the serum of mud crab, S. serrata.
Keywords: mud crab; Scylla serrata; serum; antibacterial activity; protein